Some remarks about femoroacetabular impingement and osseous non-metric variations of the proximal femur - Sébastien Villotte; Christopher J. Knüsel (Bulletins et Mémoires de la Société d’Anthropologie de Paris)
Femoroacetabular impingement is a condition of repeated contact between the acetabular rim and the femoral head-neck junction. Impingement arises as a result of abnormal morphological features involving the proximal femur (cam type) or the acetabulum (pincer type). This note illustrates the usefulness of current medical understandings of osseous modifications associated with the cam-effect in order to achieve a better understanding of osseous non-metric traits of the neck of the femur, in particular Poirier’s facet and the fossa of Allen.